The equation is $$(D^5-D)y = 12e^x$$

Here, the general solution of homogenous (D^5-D)y=0 is $y_g = c_1 + c_2 \cos x + c_3 \sin x + c_4 e^x + c_5 e^{-x}$. Now I can apply two methods:

  1. Assume particular solution to be $Axe^x$ and solve. This is linearly independant from $y_g$. But finding $D^5$ can be hectic.

  2. Use exponential shift:

$$(D^5-D)y = 12e^x\\ y = 12 e^x\frac{1}{(D+1)^5-(D+1)}(1) \\ = 12 e^x\frac{1}{(D+1)^4-1}(1)\\ = 12e^x (1+(D+1)^4 + ....)$$

This gives strange answer. What is the proper method for this?


1. More efficient way is as follows. Let us write $T=D^5-D$. For any $r\in\Bbb C$, we have $$ T[e^{rx}]=\frac{d^5}{dx^5}e^{rx}-\frac{d}{dx}e^{rx}=(r^5-r)e^{rx}. $$ Now, differentiate with respect to $r$. Then we get $$ \frac{\partial }{\partial r}T[e^{rx}]=T\left[\frac{\partial }{\partial r}e^{rx}\right]=T[xe^{rx}]=\frac{\partial }{\partial r}\left((r^5-r)e^{rx}\right)=(5r^4-1)e^{rx}+(r^5-r)xe^{rx}. $$ We get by letting $r=1$ $$ T[xe^x]=4e^x. $$ Hence, $T[3xe^x]=12e^x$ and $3xe^x$ is a particular solution of the equation.

2. In fact, correct formula should be $$ y=12(D^5-D)^{-1}[e^{x}], $$ not $$ y=12e^x (D^5-D)^{-1}[1]. $$ Note that $D^5-D=(D-1)(D^4+D^3+D^2+D)$. Since $(D^4+D^3+D^2+D)[e^x]=4e^x$, we have $$ (D^4+D^3+D^2+D)^{-1}[12e^x]=3e^x. $$ Finally, since $(D-1)[xe^x]=e^x$, we have $$ (D-1)^{-1}[3e^x]=(D-1)^{-1}(D^4+D^3+D^2+D)^{-1}[12e^x]=3xe^x. $$ This also gives a particular solution $3xe^x$.

  • $\begingroup$ sorry i dont understand your method 2 $\endgroup$ – jeea Jan 19 at 16:38
  • $\begingroup$ $$12e^x \stackrel{(D^4+D^3+D^2+D)^{-1}}\Longrightarrow 3e^x\stackrel{(D-1)^{-1}}\Longrightarrow 3xe^x.$$ $$12e^x \stackrel{D^4+D^3+D^2+D}\Longleftarrow 3e^x\stackrel{D-1}\Longleftarrow 3xe^x.$$Can you please be more specific about which part of the argument you don't understand? $\endgroup$ – Song Jan 19 at 16:42
  • $\begingroup$ Yes the first line only, from 12ex to 3ex $\endgroup$ – jeea Jan 19 at 17:27
  • 1
    $\begingroup$ @jeea Since $(D^4+D^3+D^2+D)[e^x]=4e^x$, we have $(D^4+D^3+D^2+D)^{-1}[4e^x]=e^x$. By multiplying $3$, we have $(D^4+D^3+D^2+D)^{-1}[12e^x]=3e^x$. $\endgroup$ – Song Jan 19 at 17:41
  • $\begingroup$ Oh so we have to observe and predict very carefullly $\endgroup$ – jeea Jan 20 at 4:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.